Analisis Karakteristik Gaya Belajar Mahasiswa pada Mata Kuliah Statistik Ekonomi - Puspaningrum, Cici (Economic Development Progress, 2023)
This research aims to determine the characteristics of student learning styles which consist of visual, auditory and kinesthetic learning styles. The subjects of this research were second semester students of class D in the management study program. The method used in this research is the field study method. Field research is collecting data directly in the field using data collection techniques in the form of observation, interviews and documentation studies. The results of the research show that the characteristics of student learning styles in the economic statistics course show that the most dominant student learning style is the visual type learning style. It was explained that 66.93% of students tended to have a visual learning style, 19.77% for an auditory learning style, and 13.30% for a kinesthetic learning style. This shows that the most dominant student learning style is the visual type learning style where students tend to learn by observing things. Students find it easier to remember things they see, like to scribble things that are sometimes meaningless in class, like the lecturer's explanations by showing something. The results of this research also show a combination of learning style characteristics with tendencies towards different learning style characteristics.